Transition-metal-free variant of Glaser- and Cadiot-Chodkiewicz-type Coupling: Benign access to diverse 1, 3-diynes and related molecules. Issue 16 (16th April 2020) - Kaldhi, Dhananjaya; Vodnala, Nagaraju; Gujjarappa, Raghuram; Kabi, Arup K.; Nayak, Subhashree; Malakar, Chandi C.
Graphical abstract: Highlights: Transition-metal-free approach towards Glaser- and Cadiot-Chodkiewicz-type Coupling. Regioselective synthesis of 1, 3-diynes and 1, 3-enynes. Chemical transformations were possible in aqueous medium. Organocatalyzed chemical transformations. Broad substrate scope with high yields of the products. Abstract: Efficient and transition-metal-free transformations towards the synthesis of 1, 3-diynes have been described from their corresponding terminal acetylenes or 1, 1-dibromo-1-alkenes. The efficiency of molecular iodine as catalyst in aqueous medium, driven the transformation to afford 1, 3-diynes in moderate to good yields. The developed reaction conditions revealed appreciable functional group tolerance in aqueous medium. Further, the scope of the transition-metal-free approach for the synthesis of 1, 3-enynes has been investigated using terminal alkynes as easy available precursors.